Non-Tariff Measure under WTO Laws: Case Study on the Application of Local Content Requirement for 4G LTE Devices in Indonesia - Dewi, Yetty Komalasari; Koentjoro, Talissa (Indonesian Journal of International Law, 2018)
Under the WTO laws, countries are allowed to protect their national industry by imposing tariffs as well as non-tariff measures (NTM). While the WTO is committed to reduce tariff, it does not have uniform treatment towards NTMs. One type of NTM that becomes the disputed subject of several WTO cases is Local Content Requirement (LCR) because while it can help national industry, it is seen as discriminatory towards imported products. This work discusses whether the application of the Tingkat Komponen Dalam Negeri (TKDN) or LCR provisions for 4G LTE communication devices in Indonesia is in conformity with WTO laws. By analyzing relevant WTO agreements and rulings, this work will demonstrate that Indonesia’s LCR provisions in 4G LTE sector may not be in conformity with the GATT and TRIMS but at the same time it does not violate the GATS, ASCM, and GPA because such LCR provisions do not fall under those three agreements. In light of those, this writing suggests that the government of Indonesia bring the LCR provisions in 4G LTE sector into conformity with WTO laws by revoking the provisions mandating the need to use local over imported products to avoid potential claims from other WTO members.